Management adaptation to flood in Guangdong Province in China: Do property rights Matter?. (March 2020) - Thennakoon, Jayanthi; Findlay, Christopher; Huang, Jikun; Wang, Jinxia
Highlights: Farmers with more secure property rights are more likely to take action to adapt to climate change. Security of property rights has an impact on managerial decisions concerning operational matters. Farmer adaption is influenced by government provision of public goods and by the local extent of social capital. Policy reform to add to the security of land tenure to support adaptation to climate change is important. Abstract: Improving land rights in China is often considered as an important factor that facilitates farmers' investments in agriculture. However, whether securing land rights is important for farmers' adaptation to changing climate or not has not been addressed in the literature, particularly with respect to management decisions. This paper examines the relationship between land tenure types and farmer adaptation through management decisions in response to extreme weather events in Guangdong Province in China. Based on a household survey of rice farmers, our results show that compared to a normal year with minor weather events farmers with contracted land are more likely to implement adaptation measures in response to extreme weather events than those who have rented their land from the collective and from other farmers. The results suggest that farmers' adaptive behaviour in response to extreme weather events is significantly different from their day-to-day adaptation to ongoing changes in climate. Farmers' adaptive capacity is also positively influenced by age, the public provision of information, by the presence of social capital, and by plot quality. The results of this study highlight the importance of properly defined land rights for the likelihood of adaptation, and thereby increasing agricultural productivity and ensuring food security in the context of a changing climate.